Character Strengths in E. Rokajat Asura‘s Novel Air Mata Surga - Puspita, E A (KnE Social Sciences, 2018)
This paper is concerned with character strengths in E. Rokajat Asura‘s novel Air Mata Surga. The objectives of this study is to reveal the protagonist‘s character strengths in the novel and to analyze how the protagonist‘s character strengths reflected in the novel which cover open mindedness, creativity, vitality, and gratitude. The theory adopted in this study is based on Peterson and Seligman (2004). The result of this study shows that open mindedness, creativity, vitality and gratitude are vividly reflected in the novel. This study was done by using a qualitative research method by Holliday (2007). The result of this study is theoretically significant for the readers as they can learn about the theory of character strengths as adopted in this study. This is also practically significant as it will give a contribution to the readers that they can take lessons to practice about how important it is to lead life with character strengths in order to succeed in their life. The conclusion of this study is that the most important out of the four character strengths depicted in the novel is gratitude to Allah the Almighty. Keywords: character strength, open mindedness, creativity, vitality, gratitude.